Market Costs and Financing Options for Grassland Carbon Sequestration: Empirical and Modelling Evidence From Qinghai, China - Wilkes, A.; Wang, S.; Lipper, L.; Chang, X. (Frontiers Media, 2021)
Asia’s grasslands provide livelihoods for some of the region’s poorest people. Widespread grassland degradation reduces the resilience and returns to herding livelihoods. Reversing degradation and conserving grasslands could not only improve herders’ situation, but also make a huge contribution to mitigating climate change by sequestering carbon in soils. However, the means for reaching each of these objectives are not necessarily the same. To realize this potentially huge dual livelihood/climate change mitigation outcome from improved grassland management, it is necessary to have detailed understanding of the processes involved in securing better livelihoods and sequestering carbon. Based on household surveys on the Tibetan Plateau and modeling results, this study estimates economic and market costs of grassland carbon sequestration, and analyzes the implications of household and carbon project cash flows for the design of financing options. Five scenarios are modeled involving cultivation of grass on severely degraded grassland (all scenarios) and reduced grazing intensity on less degraded land, which requires destocking by 29, 38, 47, 56, and 65% in each scenario). Modeling results suggest that economic benefits for herders are positive at low levels of destocking, and negative at high levels of destocking, but initial investments and opportunity costs are significant barriers to adoption for households in all destocking scenarios. Existing rural finance products are not suitable for herders to finance the necessary investments. Market costs–the cost at which transactions between herders and carbon project developers are feasible–depend on the scale of project implementation but are high compared to recent carbon market prices. Large initial investments increase project developers’ financing costs and risk, so co-financing of initial investments by government would be necessary. Therefore, public policies to support grassland carbon sequestration should consider the potential roles of a range of financial instruments.